2017
DOI: 10.3892/mmr.2017.7152
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of diminazene attenuates myocardial infarction in rats via increased inflammation and ACE2 activity

Abstract: The present study aimed to investigate whether diminazene attenuates myocardial infarction (MI) in rats. In addition, the present study investigated whether ACE2 signaling was involved in the effects of diminazene on protein function. A rat model of acute myocardial infarction (AMI) was established by occlusion of the left anterior descending coronary artery. The AMI model rats received intraperitoneal injections of diminazene (5 mg/kg/day) for 3 days. Treatment with diminazene significantly inhibited the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous studies have examined the connection between COX2 and MI. Chen et al found that diminazene, an antiparasitic drug, significantly reduced the expression of COX2 and the infarct area (40). Kim et al revealed that ischemic preconditioning (IPC) exerted a protective effect on MI and ischemia-reperfusion (I/R) injury, and further genetic analysis revealed that most differentially expressed genes were associated with the generation and transformation of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the connection between COX2 and MI. Chen et al found that diminazene, an antiparasitic drug, significantly reduced the expression of COX2 and the infarct area (40). Kim et al revealed that ischemic preconditioning (IPC) exerted a protective effect on MI and ischemia-reperfusion (I/R) injury, and further genetic analysis revealed that most differentially expressed genes were associated with the generation and transformation of energy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after 4 weeks of DIZE treatment in rats with myocardial infarction, DIZE improved left ventricular contractility and relaxation and prevented right ventricular high systolic pressure, also suggesting that DIZE may play an important role on cardiac dysfunction post‐myocardial infarction . However, during myocardial infarction in rats, a western blot study showed that 3 days of DIZE treatment significantly activates ACE2, AT1R and the MasR protein expression, suggesting the beneficial effect of DIZE on post‐myocardial infarction may be due to the ACE2/AT1R/MasR pathway …”
Section: The Potential Role Of Dize In Treating Vascular/endothelial mentioning
confidence: 99%
“…47 However, during myocardial infarction in rats, a western blot study showed that 3 days of DIZE treatment significantly activates ACE2, AT1R and the MasR protein expression, suggesting the beneficial effect of DIZE on post-myocardial infarction may be due to the ACE2/ AT1R/MasR pathway. 48 In addition, in the renal cortex of rats with kidney disease, subcutaneous injection of DIZE (15 mg/kg/d for 2 weeks) is associated with a reduction of cortical ACE activity and an increase in cortical ACE2 activity. 46 Interestingly, diabetic rats using streptozotocin, treatment with DIZE restored ACE2 expression in isolated glomeruli and this was associated with increased expression of AT2R.…”
Section: Dize In Cardiac and Renal Tissuementioning
confidence: 99%
“…Treatment of ex vivo hearts by administration of 10 −8 M Ang(1-7) into the bath solution using Langendorff technique re-established the impulse conduction during ischemia-reperfusion and reduced incidence of arrhythmias during IR, possibly due to cardiomyocyte hyperpolarization via the activation of sodium pump [ 89 ]. Activation of ACE2 by diminazene aceturate (DIZE) treatment [ 86 , 90 , 91 , 92 ] led to an improvement of almost all evaluated parameters (however, lacking evidence against amelioration of hypertrophy). These effects were abolished by ACE2 inhibition (“compound 16”) [ 84 , 86 ] or by Mas-receptor antagonist (A779) [ 24 , 88 ].…”
Section: Ace2 Deficiency-related Pathologies Underlying Hypoxiamentioning
confidence: 99%